Carbon Nanotubes/Heteroatom‐Doped Carbon Core–Sheath Nanostructures as Highly Active, Metal‐Free Oxygen Reduction Electrocatalysts for Alkaline Fuel Cells1. (19th February 2014) - Sa, Young Jin; Park, Chiyoung; Jeong, Hu Young; Park, Seok‐Hee; Lee, Zonghoon; Kim, Kyoung Taek; Park, Gu‐Gon; Joo, Sang Hoon
Abstract A facile, scalable route to new nanocomposites that are based on carbon nanotubes/heteroatom‐doped carbon (CNT/HDC) core–sheath nanostructures is reported. These nanostructures were prepared by the adsorption of heteroatom‐containing ionic liquids on the walls of CNTs, followed by carbonization. The design of the CNT/HDC composite allows for combining the electrical conductivity of the CNTs with the catalytic activity of the heteroatom‐containing HDC sheath layers. The CNT/HDC nanostructures are highly active electrocatalysts for the oxygen reduction reaction and displayed one of the best performances among heteroatom‐doped nanocarbon catalysts in terms of half‐wave potential and kinetic current density. The four‐electron selectivity and the exchange current density of the CNT/HDC nanostructures are comparable with those of a Pt/C catalyst, and the CNT/HDC composites were superior to Pt/C in terms of long‐term durability and poison tolerance. Furthermore, an alkaline fuel cell that employs a CNT/HDC nanostructure as the cathode catalyst shows very high current and power densities, which sheds light on the practical applicability of these new nanocomposites.